THE CHANGE OF INDONESIANS LIFESTYLE TOWARDS FOOD PURCHASE DECISION DURING COVID-19 PANDEMIC - Amira Nurul Azmi; Genoveva Genoveva (President University, 2021)
Since the earlier of 2020, Indonesia has been fighting against Covid-19 and currently there have been more than four thousand people infected by Covid-19 per day. This raises fears of all sectors especially in business. All regulations and policies such as social distancing, health protocols, work from home, travel restrictions, and self-isolation at home have been implemented by the government. As a result, all workforce must be reduced in all economic sectors, which causes an increase in the number of unemployed. If schools and offices are closed, some of the populations are influenced to change their life into a healthy lifestyle in order to prevent any disease that will come to them. This case will impact to their trust towards the food-seller and they will decide whether they purchase or not. Hence, this research explains about the influence of the lifestyle towards purchase decision through customer trust as the mediating variable. The variables of this research such as the dimensions of lifestyle (activity, interest, and opinion) as independent variables, purchase decision as dependent variable, and customer trust as the mediating variable. This research is a quantitative research which using SmartPLS 3.0 (Partial Least Square Structural Equation Model). The online questionnaire spread to 171 respondents by snowball sampling. The result show that the positive influence of lifestyle (activity, interest, and opinion) on purchase decision. In additional, the lifestyle positive influence on purchase decision trough trust as the intervening variable. Keywords: lifestyle, customer trust, purchase decision, covid-19.